Kontrol Diri dengan Perilaku Agresif Siswa SMA Negeri 1 Trimurjo Kabupaten Lampung Tengah - Indah Dwi Cuyunda; Octa Reni Setia; Sri Maria Puji Lestari; Prambudi Rukmono (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: adolescence is a transition from childhood to adulthood, during this time juvenile delinquency is very prevalent as aggressive behavior. One form of aggressive behavior that often occurs among teenagers is brawled between students, basically, delinquency and aggressiveness in adolescents, especially brawl behavior can occur due to the failure of adolescents to control themselves. Purpose: This study agrees to find out the relationship between self-control and aggression in Trimurjo Stage 1 High School Student Central Lampung Regency. Research Method: Quantitative research with analytic design and cross-sectional design and Simple Random Sampling sampling techniques. Data were evaluated with SPSS. The result: 205 samples out of 500 populations, median values 82.00 (moderate), min-max values (52-120) for self-control and median values 79.00 (moderate), min-max values (43-99) for aggressive behavior. The results of the Bivariate Spearman test showed a P-Value of 0.021, and an r-value of - 0.161. Conclusion: There is a significant relationship between self-control and aggressive behavior inTrimurjo1 Lampung Tengah High School students, with low correlation strength and negative correlation direction, namely the higher the self-control, the lower the person's aggressive behavior.